Batch optimization of biogas yield from pasteurized slaughterhouse by-products incorporating residues from corn sieving - Galván, María José (2021)
Batch anaerobic digestion of pasteurized pig slaughterhouse waste (SW) and corn sieving waste (CSW), and anaerobic co-digestion of CSW/SW were studied at lab scale employing several carbon to nitrogen ratio (C/N) and total solids (TS) content. The mixtures with highest biogas yield and suitable process inhibition parameter values were used to scale up to pilot scale. The results showed that SW and CSW co-digestion improved biogas yield in comparison with that obtained from mono-digestion of both substrates. Thus, it is possible to ensure that the CSW is a proper substrate to balance C/N and improve biogas yield. Moreover, this study reveals that the best biogas yield for each C/N mixture is achieved using the lowest TS content. Also, the SW/CSW mixture with C/N 15 and 5% TS achieved the highest biogas yield and the best inhibition parameters values. The pilot scale assay demonstrates that biogas yield, methane yield and Organic Matter Removal for C/N 15 mixture were 41%, 25%, and 24% higher than those using C/N 20, respectively, and the H2, CO2 gasses composition presented variations. However, the methane content was similar for both C/N 15 and C/N 20 at pilot scale.